RECEPTION OF THE QUR’AN IN THE DIGITAL AGE: SOCIAL MEDIA ONLINE RUQYAH ON MUHAMMAD FAIZAR’S YOUTUBE VIDEOS - Nabila, Ida Fitri (Tanzil: Jurnal Studi Al-Quran, 2024)
Online Ruqyah is a new phenomenon that has emerged since the digital era began to develop rapidly. Ruqyah, which has been understood and generally practiced in a limited time and scope, is no longer understood as such with the presence of various social media platforms. One of the ruqyah practitioners who utilizes social media as a means of da’wah is Muhammad Faizar. Faizar is one of the pioneers of the spread of ruqyah in Indonesia, and he is present on television. He is also one of the first ruqyah practitioners to use social media as a means of ruqyah. On the YouTube platform, Faizar uploaded a new alternative in the world of ruqyah, namely the practice of online ruqyah. The practice is carried out by uploading videos of ruqyah readings. This paper aims to look at the reception of the living Qur’an that is reflected in it and the extent to which ruqyah can work even though it is done virtually. This research is qualitative and analyzed using the reception theory initiated by Ahmad Rafiq. The results of this study show that ruqyah performed virtually (online ruqyah) can also show its function, namely exegesis and functional reception. Functional reception in the context of Muhammad Faizar’s online ruqyah is informative and performative. Even though they did not meet the ruqyah practitioner directly, some online ruqyah listeners felt the benefits of sharing their online ruqyah experience in the comment column.